STUDI PENGEMBANGAN SDM MELALUI KAJIAN TENTANG PENGARUH DISIPLIN DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI SISWA Studi Kasus SMU Bina Bangsa Sejahtera, Bogor - Hasanul Arifin (STIE Binaniaga, 2005)
The study is aimed at finding out the influence of students’ learning discipline and learn-ing environment, either physical or non-physical to the learning achievement.The research had been done since they were in the first grade till they were in the third grade, for around two a half years. Data collection was done in January and February 2003, either primary or se-condary. The research population is all students of IPA programmers (IPA-1 and IPA-2), consisting of 78 students.Data collected are their marks in their report books, from grade one to grade three, their time management, responsibility, daily behaviour, learning target, physical environment condition, the use of media and teachers motivation. The data was tabulated and analyzed with statistical analysis, by the use of SPSS programme. The research result shows that learning discipline and environment all together significantly influence the students’ achievement. This can be seen from the result of F- test (199.434) > F tabel (3.0718), or probality F (0.000) <  (0.05). But partially, learning environment gives a significant influence to the learning achievement (t-test=18.512 > t-tabel =1.980 or probibility=0.000 < =0.05), while learning discipline does not (t-test=0.123 > t-tabel =1.980 or probibility=0.902 <  =0.05)The regression square test shows that the standardized coefficient beta for the learning discipline variable is 0.006 and learning environment variable is 0.415. The test result shows that both variables give a significant influence. Although the learning environment is higher, the coefficient correlations show the possitive ones (R=0,917). Therefore, it can be concluded that the higher the students’ learning disci-pline and the more conducive of learning enviranment, the better the students’ achievement. The variety of learning achievement caused by the variety of learning disipline and environment is 84,2%, as shown by R-square change (0.842). Statistically, this implies that the rest (15,8%) is influenced by other factors. The other factors, to the writer,might be parents. Intellegence, relationship to friends and students’ phy-sical condition.